Observation of vector solitons supported by third-order dispersion - Guo, Jun (2019)
We report on the experimental observation of dark-bright and antidark-bright vector solitons supported by third-order dispersion in a weakly birefringent cavity fiber laser. Using a cavity dispersion and birefringence management technique we constructed a weakly birefringent cavity fiber laser with near-zero net cavity dispersion. Operating the fiber laser in either the net normal or net anomalous dispersion regime, we found that both dark-bright and antidark-bright vector solitons could be simultaneously formed as a result of incoherent cross-polarization phase modulation. Our experimental results confirm the existence of antidark-bright vector solitons and the coexistence of dark-bright and antidark-bright vector solitons in a real physical system.